Manifestation experiences in hotel units. An analysis of Machu Picchu’s hotels reviews on TripAdvisor network - Galhardo, Andreia (2020)
This paper describes the image of hotels transmitted by customers on the social network TripAdvisor.es. It is a case study that breaks down and interprets the analysis of a set of comments in the Spanish language to 20 hotels in Machu Picchu (Peru). Moreover, we did a descriptive analysis, based on the inference of qualitative and quantitative data, to 177 comments of the aforementioned social network, distributed by the first 20 hotels listed in order of classification of the traveler, between the months October to December 2019. The comments were analyzed through a table composed of 14 categories and we observed that positive commentaries prevail in all categories, and that the experiences most appreciated by travelers and described in our sample were “Service”, “Food”, and “Location”.